The Response to Growth and Yield of Sweet Corn due to the use of Azospirillum sp and N fertilizer on Peat Soil - Pratama, Ikhsan Wahyu (Fakultas Pertanian Universitas Tanjungpura, 2021)
Azospirillum sp are non-symbiotic bacteria that can fix N from the air. Urea is a fertilizer that contains macro nutrients, namely nitrogen. This study aims to determine the interaction between Azospirillum sp and the best dose of urea for the growth and yield of sweet corn on peat soil. This research was conducted in Rasau Jaya 2, Patok 34, Wonosari Village from 7 October - 16 December 2020. This study used a factorial randomized block design (RBD) with 2 factors. The first factor is Azospirillum sp with 2 levels, without the application and the application of Azospirillum sp. The second factor is the dose of urea fertilizer with 4 levels, namely 75 kg / ha, 150 kg / ha, 225 kg / ha and 300 kg / ha. The variables observed in this study were plant height, plant dry weight, total leaf area, root volume, diameter of corn cobs, length of corn cobs, weight of corn with husks, weight of corn without husks and weight of corns per plot. There is an interaction between Azospirillum sp and urea fertilizer on the variable weight of corn with husks and the best treatment combination is found in the application of Azospirillum sp and urea fertilizer at a dose of 75 kg / ha. The application of Azospirillum sp gave a significant effect on the variables of total leaf area, weight of corn without husks, diameter of corn cobs and weight per plot. The urea fertilizer treatment had a significant effect on the weight of corn with husks and the diameter of corn cobs, the best dose was found in the urea fertilizer treatment is 75 kg / ha.